Analysis of The Influence of Economic Growth, Foreign Investment, And International Trade on Income Inequality in Indonesia in The Period of January 2005 To December 2013 - Refika Tiara (The Eastasouth Management and Business, 2022)
The purpose of this study is to find out how the response was given by the Gini coefficient variable to the movement of the variables of economic growth, foreign capital flows, and international trade and to find out which variables make the largest contribution to the amount of investment credit, the authors choose the Vector Auto Regression (VAR) analysis tool. ) or Vector Error Correction Model (VECM). IRF results show that when there is a movement in the economic growth of 1 standard deviation, the Gini coefficient responds negatively. This shows that when there is an increase in economic growth, the Gini coefficient will decrease. According to the Trickle-Down Effect theory, The increase in economic growth enjoyed by some of the rich will ultimately affect the economic activities of the poor and this growth will be enjoyed by the poor. The IRF results show that when there is a movement in the number of foreign capital inflows into Indonesia by 1 standard deviation, the Gini coefficient trend will respond positively. The increase in MNCs due to increased FDI causes an unequal distribution of income. This is because MNCs employ only skilled labor so that only some highly skilled workers get additional income and the income distribution becomes unequal. The impact of international trade can harm income inequality due to a large number of import activities carried out by Indonesia, thereby reducing the competitiveness of domestic producers. This reduces the income of local producers and causes an unequal distribution of income.